Community volunteers in Japan : everyday stories of social change - Nakano, Lynne Y., 1965- (Japan anthropology workshop series., 2005)
"Volunteering is a recent and highly visible activity in Japan practiced by millions of Japanese, and covered widely in the Japanese media. This book, based on extensive original research, explores volunteering in an urban residential Japanese neighbourhood. It discusses the activities volunteers engage in, their experiences and their motivations, and argues that personal decisions to volunteer, besides being personal choices, also reflect national level discussions of the needs and directions of Japanese society."--Jacket